O22.2 Detection of hepatitis c virus (hcv) in semen from hiv-infected men who have sex with men (msm) during acute hcv infection. (13th September 2015) - Turner, S; Yip, M; Smith, D; Weibel, S; van Seggelen, W; Foster, A; Morey, T; Barbati, Z; Branch, A; Fierer, D
Abstract : Introduction: The mechanism(s) and bodily fluid(s) involved in the recently identified epidemic of sexually transmitted HCV in HIV-infected MSM are unclear. HCV is present only intermittently and at low levels in semen from men with chronic HCV-infection, however little is known of the dynamics of seminal HCV during acute HCV-infection. Methods: HIV-infected MSM with acute and chronic HCV-infection were prospectively enrolled into an IRB-approved study.  Three paired semen and blood specimens were collected at 2-week intervals.  HCV viral load (VL) was quantified using an automated RT-PCR assay platform (Abbott). Results: Paired semen and blood specimens were obtained from 33 HIV-infected MSM (21 with acute-HCV and 12 with chronic-HCV). Sixteen (27%) of 59 semen specimens had detectable HCV VL, with 11 (33%) men having at least one positive specimen. Semen specimens with detectable HCV had a significantly higher median blood HCV VL (P = 0.002). There were no differences between men with acute or chronic HCV in either the proportion of semen specimens positive for HCV (8/38 [21%] and 8/21 [38%], respectively; P = 0.159), or in the median seminal HCV VL (1.32 log IU/ml and 1.77 log IU/ml, respectively; P = 0.163). Conclusion: This study, although identifying no differences in the magnitude or proportion of seminal HCV during acute HCV-infection, provides valuable insights into the dynamics of seminal HCV during this period. It is unknown whether the levels of seminal HCV identified in this study are sufficient for the sexual transmission of HCV in HIV-infected MSM. However, it is plausible that HCV in semen deposited in the rectum after the friction of receptive anal intercourse, could enter the blood stream and infect the liver. Future research should focus on establishing the infectivity of seminal HCV, and the analysis of seminal HCV levels during the `ramp-up' period of early acute HCV-infection, where blood HCV levels are highest. Disclosure of interest statement: There are no competing or financial interests to disclose.